ESTETIKA PERTUNJUKAN DRAMA TRADISIONAL CUPAK GURANTANGDI SANGGAR DEWI ANJANI DUSUN KELOTOK DESA WAKAN KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR- - Rahmani, Uhya Ruri Yuapi; Yuliatin, Riyana Rizki; Imtihan, Yuspianal (Universitas Hamzanwadi, 2021)
This study aims to describe the aesthetics of the traditional drama performance of Cupak Gurantang in Kelotok Village, Wakan Sanggar Seni Dewi Anjani Village. The approach used in this study is a qualitative method. The aesthetic value in the traditional drama performance of Cupak Gurantang can be seen in terms of form, content and appearance. The form of the traditional drama drama Cupak Gurantang appears in aspects that support the performance which consists of forming elements such as, theme, setting / setting, plot, language, character and characterization, mandate, and supporting elements such as, stage layout, make up and fashion, lighting or lighting, and sound system. The component form of the performance gives a dynamic impression so that the message to be conveyed is received by the audience. The contents of the show can be seen from the ideas or ideas that come from the theme of the story, the atmosphere that is displayed, and the message that contains human values that can be an example for social life. Appearances are seen from the talents and skills of the traditional drama drama Cupak Gurantang.